[
next
] [
prev
] [
prev-tail
] [
tail
] [
up
]
2
Examples
2.1
\(9p^{2}\left ( 2-y\right ) ^{2}=4\left ( 3-y\right ) \)
2.2
\(p^{2}=xy\)
2.3
\(27y-8p^{3}=0\)
2.4
\(y-2xp-\ln p=0\)
2.5
\(y-x\left ( 1+p\right ) -p^{2}=0\)
2.6
\(y-2xp-\sin \left ( p\right ) =0\)
2.7
\(y-p^{2}x+\frac {1}{p}=0\)
2.8
\(xp+p-p^{2}-y=0\)
2.9
\(y=px+\sqrt {4+p^{2}}\)
2.10
\(p^{2}-xp+y=0\)
2.11
\(p=y\left ( 1-y\right ) \)
2.12
\(p^{2}x+py\ln y-y^{2}\left ( \ln y\right ) ^{4}=0\)
2.13
\(p^{2}-4y=0\)
2.14
\(1+p^{2}-\frac {1}{y^{2}}=0\)
2.15
\(y-p^{2}+3xp-3x^{2}=0\)
2.16
\(p^{2}\left ( 1-y\right ) ^{2}-2+y=0\)
2.17
\(\left ( y-xp\right ) ^{2}-p^{2}=1\)
2.18
\(y=xp+ap\left ( 1-p\right ) \)
2.19
\(p^{3}-4xyp+8y^{2}=0\)
2.20
\(4xp^{2}=\left ( 2x-1\right ) ^{2}\)
2.21
\(p=2x\left ( 1-y^{2}\right ) ^{\frac {1}{2}}\)
2.22
\(p^{2}+2xp-y=0\)
2.23
\(p^{2}\left ( 2-3y\right ) ^{2}-4\left ( 1-y\right ) =0\)
2.24
\(8p^{3}x=y\left ( 12p^{2}-9\right ) \)
2.25
Clairaut
\(y=xp+a\sqrt {1+p^{2}}\)
2.26
Clairaut
\(y=xp-e^{p}\)
2.27
\(p^{2}\left ( 1-x^{2}\right ) =1-y^{2}\)
2.28
\(y^{2}\left ( 1+p^{2}\right ) =4\)
2.29
Clairaut
\(y=px-\arcsin \left ( p\right ) \)
2.30
\(4xp^{2}=\left ( 3x-b\right ) ^{2}\)
2.31
\(4p^{2}x\left ( x-A\right ) \left ( x-B\right ) =\left ( 3x^{2}-2x\left ( A+B\right ) +AB\right ) ^{2}\)
[
next
] [
prev
] [
prev-tail
] [
front
] [
up
]